Strengthening the Language of Love as a Prevention Measure School Bullying Prevention - Pasmawati, Hermi; Afriyati, Vira; Sari, Intan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
Bullying in schools is a complex problem that requires serious attention. This study aims to examine the potential for strengthening love language as one of the effective prevention efforts in bullying cases in schools. The study focuses on literature that discusses the relationship between love language, positive social bonds, and prosocial behavior. The methodological procedure of this article uses a literature review approach. The results of the study show that love language with indicators of affirmative words, acts of service, gifts, quality time, and physical touch has great potential in creating an inclusive and supportive school climate. This study also identifies several factors that can affect the success of the implementation of love language in efforts to prevent bullying in schools, namely; training for educators, parent involvement, and support from the school environment. The practical implications of this study are the importance of integrating love language in school curricula and counseling programs to prevent and overcome bullying in schools.